(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
This paper, through random references to select African fictions, aims to highlight how literature represents and advocates for democracy and the rule of law in Africa. The paper deploys intertextuality as its theoretical guide and the text-based method as its analytical tool. It is found that democracy implies a process of constitutional delegation of the supreme power that is vested in the people and exercised by them through a system of representation usually involving periodic popular elections, while the rule of law is the political philosophy which holds that all citizens and institutions within a country, regardless of social statuses, are not only equal, but also accountable to the same laws. It establishes that literature is simply a cultural reflection of the daily developments of a people through time and space which has aesthetic value, historical significance, cultural refinement and the envisioning of future cultural prospects through cultural rejuvenations. In other words, literature imaginatively mirrors the society’s socioeconomic and political transformations through time and space while providing encoded solutions to existential problems. It is also established that, African literature has consistently critiqued politics, democracy and the act of political governance due to inherently glaring abuse, procedural manipulation and open neglect of the rule of law. The paper concludes that the only feasible route to sustainable democracy and development in Africa is the enunciation of the philosophy of liberal democracy which gives precedence to the rule of law.